Evaluation of the Urban regions of Serbia - Živanović, Zora; Tošić, Branka; Gataric, Dragica (Geographica Pannonica, 2020)
The subject of this paper is an evaluation of defined urban regions in Serbia, with an aim towards identifying their basic features, with special emphasis on the measurement of their functional polycentricity. These features include methods with following indicators: share of settled inhabitants to overall population number in the centre of urban region and surrounding area, according to the outcome; concentration level of employees in centres and structure of activities of active population performing an occupation, functional dependence of settlements in the area of the region and determining the functional polycentricity index of the urban region. Therefore, the goal of the paper is to clarify the difference between the urban regions that have developed in the area of Serbia, which are significant factors for further planning of polycentric and balanced regional development. The results of the survey show differences between urban regions, primarily by the degree of functional polycyclicism, but also according to other criteria.